Streptococcus pneumoniae serotype 19A: worldwide epidemiology - Raul Isturiz; Heather L Sings; Betsy Hilton; Adriano Arguedas; Ralf-René Reinert; Luis Jodar (Taylor & Francis Group, 2017)
Introduction: Streptococcus pneumoniae causes mucosal and invasive diseases with high morbidity and mortality. Introduction of the 7-valent pneumococcal conjugate vaccine (PCV7) into routine infant immunization programs worldwide resulted in serotype 19A becoming a leading cause of the remaining pneumococcal disease burden in vaccinated and nonvaccinated individuals. This article reviews the impact of the latest generation PCVs (10-valent PCV, PCV10, and 13-valent PCV, PCV13) on serotype 19A. Areas covered: This article covers immune responses elicited by PCV7, PCV10 and PCV13 against serotype 19A and their impact on nasopharyngeal (NP) carriage and disease in vaccinated and unvaccinated populations using data from surveillance systems, randomized controlled trials, and observational studies. Expert commentary: As expected from a PCV containing serotype 19A, PCV13 elicits significantly higher functional immune responses against serotype 19A than PCV7 and PCV10. Higher responses are likely to be linked to both direct impact in vaccinated populations and reductions in 19A NP carriage in children, thus inducing herd protection and reducing 19A invasive pneumococcal disease (IPD) in nonvaccinated children and adults. In contrast, PCV7 and PCV10 have shown mixed evidence of direct short-lived cross-protection and little to no impact on 19A carriage, resulting in continued transmission and disease.